Tube ileostomy for faecal diversion in elective distal colorectal anastomosis: a systematic review and pooled analysis. (August 2015) - Nachiappan, S.; Datta, U.; Askari, A.; Faiz, O.
Abstract Aim Tube ileostomy may be an alternative technique to loop ileostomy for protection of distal anastomosis, but its evidence base has not yet been established. This systematic review aims to evaluate the use of tube ileostomy and compare the outcomes associated with it. Method A systematic literature search of MEDLINE, EMBASE, Web of Science and the Cochrane database was conducted. Studies reporting on elective left‐sided/colorectal anastomosis were included. Studies which reported on emergent surgery, small bowel anastomosis or tube ileostomy as a bridging procedure were excluded. The intra‐operative technique, postoperative management and complications were assessed. Outcome measures included anastomotic leak, reoperation and complications related to the stoma or tube ileostomy. Results Seven studies met the inclusion criteria. Three were case series with 101 patients and four were nonrandomized comparative studies with 665 patients. Pooled analyses of three comparative studies, comparing tube ileostomy (n = 278) with loop ileostomy (n = 254), revealed no significant differences in anastomotic leak rates (pooled OR 0.85, 95% CI 0.41–1.75; I2 = 0%, P = 0.43). Conclusion There is a re‐emergence of interest in the use of tube ileostomy to defunction a distal anastomosis. Pooled analyses of studies comparing tube ileostomy with loop ileostomy do not show statistically significant differences in anastomotic leak rates. Further refinement of this technique and randomized controlled studies are necessary for this technique to be routinely taken up by surgeons.